DINAMIKA HUKUM ISLAM DAN POLITIK LUAR NEGERI RUSIA - M. Sya?roni Rofii (LPPM STAI DARUSSALAM LAMPUNG, 2012)
The development of Islam throughout the world so rapidly. This thencreates its own dynamics when it?s met with the traditions of each country.In Russia, Islam is looking for balance, it?s began to have a place in policymakingtables. Russia is also nowadays build a positive image on the worldstage as part of long-term plan. This paper presents about the phenomenon,as well as the Russians began to embrace Islam and make Islam both atdomestic and international level as two inseparable part.